Jordan : Report on Observance of Standards and Codes-Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2006)
This paper examines the Report on the Observance of Standards and Codes on Jordan's fiscal transparency. Government activities are generally distinguished from those of public financial institutions, which carry out quasi-fiscal activities. Government holdings of fully owned corporations, and equity participations are moderate, but the management of state assets is not defined clearly, and the monitoring system is inadequate. Quasi-fiscal activities have been particularly prominent in the energy sector, related to the maintenance of fuel prices below world prices.